Autoantibodies to Apolipoprotein A-1 in Cardiovascular Diseases: Current Perspectives. (20th November 2012) - Teixeira, P. C.; Cutler, P.; Vuilleumier, N.
Abstract : Immune-mediated inflammation plays a major role in atherosclerosis and atherothrombosis, two essential features for cardiovascular disease (CVD) development, currently considered as the leading cause of death in the western world. There is accumulating evidence showing that humoral autoimmunity might play an important role in CVD and that some autoantibodies could represent emerging cardiovascular risk factors. Recent studies demonstrate that IgG autoantibodies against apolipoprotein A-1 (apoA-1) are raised in many diseases associated with a high cardiovascular risk, such as systemic lupus erythematosus, acute coronary syndrome, rheumatoid arthritis, severe carotid stenosis, and end-stage renal disease. In this work, we aimed at reviewing current data in the literature pointing to anti-apolipoprotein A-1 antibodies (anti-apoA-1 IgG) as a possible prognostic and diagnostic biomarker of cardiovascular risk and appraising their potential role as active mediators of atherogenesis.